2010
DOI: 10.1093/annonc/mdp304
|View full text |Cite
|
Sign up to set email alerts
|

Association between gain-of-function mutations in PIK3CA and resistance to HER2-targeted agents in HER2-amplified breast cancer cell lines

Abstract: PIK3CA mutations are associated with resistance to HER2-targeted agents. PI3K inhibitors are potentially effective in overcoming trastuzumab resistance caused by PIK3CA mutations. S6K phosphorylation is a possibly useful pharmacodynamic marker in HER2-targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 36 publications
5
147
1
5
Order By: Relevance
“…(44) NF-kB activation in breast cancer cells has been shown to increase trastuzumab resistance, (45) supporting the idea of NF-kB as a potential target in trastuzumab-resistant breast cancers. Our results of significant nuclear accumulation of p65 (RelA), the most predominant active complex of NF-kB family in epithelial cells in association with p50 subunit, indicate that NF-kB pathway is functional in resistant cells.…”
Section: Mechanism Of Nf-jb Activation In Trastuzumab-resistant Cellsmentioning
confidence: 81%
See 1 more Smart Citation
“…(44) NF-kB activation in breast cancer cells has been shown to increase trastuzumab resistance, (45) supporting the idea of NF-kB as a potential target in trastuzumab-resistant breast cancers. Our results of significant nuclear accumulation of p65 (RelA), the most predominant active complex of NF-kB family in epithelial cells in association with p50 subunit, indicate that NF-kB pathway is functional in resistant cells.…”
Section: Mechanism Of Nf-jb Activation In Trastuzumab-resistant Cellsmentioning
confidence: 81%
“…Moreover, the up-regulation of the HER2 downstream signal pathway is another cause of trastuzumab resistance. PTEN loss (36,53) has been implicated in trastuzumab resistance by increasing PI3K/Akt (33,45) and activating IL-6 to mediate cancer stem cells. (29) Our data have established that the activation of PI3K/Akt pathway is sensitive to the NFkB inhibitor in resistant cells.…”
Section: Mechanism Of Nf-jb Activation In Trastuzumab-resistant Cellsmentioning
confidence: 99%
“…Albeit the impact of these mutations concerning patient outcome is not completely clear yet, it has been reported that PI3K hyperactivity contributes to a lower response to trastuzumab and lapatinib treatment in patients with HER2-positive tumors (Berns et al, 2007;Eichhorn et al, 2008;Serra et al, 2008;Kataoka et al, 2010) as well as to resistance to anti-estrogen therapies. Furthermore, mutations regarding exon 20 of PIK3CA have been associated with poor prognosis (Lai et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…T47D cells carry a point mutation in exon 20 leading to an amino acid change at position 1047 (H1047R). Finally, SKBR-3 cells were reported to exhibit no PIK3CA mutations at these positions (Hollestelle et al, 2007;Jensen et al, 2011;Kataoka et al, 2010;Weigelt et al, 2011). In the beginning, primer sets for exon amplification described in Hurst et al (2009) were used but gave non-satisfying results within our setting.…”
Section: 2mentioning
confidence: 94%
See 1 more Smart Citation